Boiler dynamics and control in nuclear power stations proceedings of the international conference organized by the British Nuclear Energy Society held on 22-23 March 1973 at the Institution of Civil Engineers, London. (Thomas Telford, 1973)
Proceedings of an international conference held on 22-23 March 1973.